Evaluation of Indicators of the State of the Body Obtained During Medical and Pedagogical Observations - Yakubova Guyokhon Kuchkarovna; Sidiqov Shoyadbek (Genius Journals, 2023)
At the present stage of the rapid development of sports, higher requirements are offered to the body of athletes. Assessment of the functional state at various stages of training is the main task of a sports doctor. With the development of new technologies in sports, new opportunities appear, first of all, for express assessment of the functional state of the cardiovascular system.
Keywords: cardiovascular; appear; sports; requirements